Home-based exercise for people living with frailty and chronic kidney disease: A mixed-methods pilot randomised controlled trial. - Andrew C Nixon (Public Library of Science (PLoS), 2021)
Background Frailty is associated with adverse health outcomes in people with chronic kidney disease (CKD). Evidence supporting targeted interventions is needed. This pilot randomised controlled trial (RCT) aimed to inform the design of a definitive RCT evaluating the effectiveness of a home-based exercise intervention for pre-frail and frail older adults with CKD. Methods Participants were recruited from nephrology outpatient clinics to this two-arm parallel group mixed-methods pilot RCT. Inclusion criteria were: ≥65 years old; CKD G3b-5; and Clinical Frailty Scale score ≥4. Participants categorised as pre-frail or frail using the Frailty Phenotype were randomised to a 12-week progressive multi-component home-based exercise programme or usual care. Primary outcome measures included eligibility, recruitment, adherence, outcome measure completion and participant attrition rate. Semi-structured interviews were conducted with participants to explore trial and intervention acceptability. Results Six hundred and sixty-five patients had an eligibility assessment with 217 (33%; 95% CI 29, 36) eligible. Thirty-five (16%; 95% CI 12, 22) participants were recruited. Six were categorised as robust and withdrawn prior to randomisation. Fifteen participants were randomised to exercise and 14 to usual care. Eleven (73%; 95% CI 45, 91) participants completed ≥2 exercise sessions/week. Retained participants completed all outcome measures (n = 21; 100%; 95% CI 81, 100). Eight (28%; 95% CI 13, 47) participants were withdrawn. Fifteen participated in interviews. Decision to participate/withdraw was influenced by perceived risk of exercise worsening symptoms. Participant perceived benefits included improved fitness, balance, strength, well-being, energy levels and confidence. Conclusions This pilot RCT demonstrates that progression to definitive RCT is possible provided recruitment and retention challenges are addressed. It has also provided preliminary evidence that home-based exercise may be beneficial for people living with frailty and CKD. Trial registration ISRCTN87708989; https://clinicaltrials.gov/.